The barcodes of finance - Grody, Allan D (Henry Stewart Talks, 2018)
In this interview Allan Grody describes his experiences during a long term (and ongoing) campaign to seek adoption of a system to enable the assessment of aggregated systemic risk in the trading and settlement of global financial transactions. The proposal called, colloquially, ‘The Barcodes of Finance’ is based on the system used to track manufactured products (GS1), with identifiers of organisations, products and contracts integrated into a single system. The interview covers the problems of effecting change in global market practice when regulators are national organisations and the largest participating corporations are global. The interview discusses who can influence and make policy and the difficulties of ensuring implementation of change in depth. Mr Grody argues that present policy is repeating the mistakes of the past and is developing systems that will not prove fit for purpose. The interview illustrates the difficulties of securing adoption of global standards in an interconnected world where power is widely distributed, technical knowledge among decision makers is limited and vested commercial interests abound. “Overview” provided by Mr Allan Grody: The proposed ‘Barcodes of Finance’ is unlike the regulators’ currently designed system. The regulators’ system requires all the world’s financial regulators, there are about 200, to compel financial industry market participants to implement the system. The proposal would, instead be implemented by Global Systemically Important Financial Institutions (G-SIFIs). There are 40 such financial entities overseen by some 12 regulators. These G-SIFIs do business with nearly all financial market participants. Like Walmart, Fed Express, Amazon, et al that demand use of Barcodes by their supply chain participants, in similar manner G-SIFIs would demand use of the Barcodes of Finance in order to do business with them. The G-SIFIs would recoup their implementation costs through operational process cost reduction and risk mitigation (the latter recognized through regulators’ granting operational risk capital reductions, an already established regulatory incentive that could be used here). These benefits were the reason the industry and its trade associations went along with the regulator’s need for data standards for their own risk data aggregation requirements. The current rollout of the regulators’ designed system focuses exclusively on regulatory reporting of financial transactions, leaving the financial industry to achieve benefits far into the future, if ever. The rollout of the Barcodes of Finance would be driven by a government/industry not-for profit utility, not unlike the current regulatory sponsored approach. However, it would be overseen by far fewer regulators, there are currently 70 in a committee that represents the approximately 200 financial regulators that are expected to voluntarily enforce the financial market participant standard, the Legal Entity Identifier (LEI). There are only a dozen regulators who would need to offer the operational risk capital incentive and, in turn, compel the G-SIFI’s to take this on. The current approach to the LEI is presently organized around 32 local operating units (LOUs), a collection of many types of public and private entities - patent office, central securities depository, payment network collective, business registrar, central bank, software companies, data vendors, GS1 member organizations, etc. Each LOU is independent of the other. They interface with the financial market participant and attempt to verify their inputs – basically name and address information, by accessing secondary sources of this data - business registers, data vendors, public announcements, etc. They then assign a globally unique code, one each to each business entity in a company. This code has no relation to each other for the same parent entity. The data and the code are placed into a data base at each LOU and transmitted each day to a central facility where it is made available as free data to all. The standard and governance structure for the Unique Product Identifier (UPI) and the Unique Transaction Identifier (UTI) has yet to be finalized even though the UPI has been rolled out in the EU through a new software entity, overseen by the Association of National Numbering Agencies, with flaws already apparent. Data aggregation for risk purposes was the overriding objective for creating standard codes. The current approach to data aggregation for the LEI is to be accommodated by accessing another data base, one which associates each code with its ultimate and immediate parent. This approach substitutes for aggregation of associated financial transactions directly from the transaction itself. Instead aggregation must first proceed by looking up a series of codes on the central data base and then find each on the parent database. The complete hierarchy of parent-child legal entities for each ultimate parent must follow the accounting industry’s account consolidation rules for financial statement reporting. The proposed Barcodes of Finance alternative for he LEI was to distribute globally unique prefixes to each financial market participant. Thereafter each so designated financial market participant would apply their own suffix to complete the code for each of their subsidiaries and their products. A legal entity’s auditors would be required to verify the data at its source. They would also be the trusted source to advise and verify the organization’s hierarchy, which, right now is to be done by the LOU referencing secondary sources. At this time, LOUs have only been able to carry out this function 30% of the time, relying on the submitting entity to register this information without any check on the validity of this information. There is a similar issue with the UTI. It is being issued in real-time with 100% of the reference data supplied directly by financial firms but with no validation required. The proposed Barcodes of Finance would have oversight of the LEI by its auditors or designated accountants. In conjunction with the legal entity, they would place the required name and address information along with the completed code directly into the system for each legal entity. Where trading protocol or regulation requires anonymity encrypted prefixes designating the parent entity would be entered. This at-source entry would allow for a completely electronic straight-through-processing process. The multiple LOUs that impose another layer of financial intermediaries into the global financial infrastructure, would be redundant. A single virtually connected networked utility disbursed across required sovereign jurisdictions, as the Internet is structured, would replace this legacy wheels (LOUs) and hub (central data base) Rube Goldberg structure. This architecture perpetuates the best practices of the past, not the industry’s digital future. The current systems architecture represents, yet again, the legacy thinking of an industry and its regulators. In fact, the Internet-like architecture of the Barcodes of Finance was proposed and accepted by the Financial Stability Board (FSB), the global standards setter given the responsibility to oversee the regulators in implementing financial standards. The FSB itself is overseen by the G-20, the global entity comprised of the 20 leaders of the world’s largest economies. However, the implementation of this technology architecture was thwarted, politics and vested interests prevailed. This same legacy architecture is being applied to the newly developed trade repositories (there are 25). Financial transactions are being reported with the new data standards so they can be accumulated and aggregated for regulatory risk analysis. This has yet to be achieved as the data standards already in place are proving dysfunctional. Both the LOU and trade repository approaches are coming under scrutiny by industry trade associations and regulators alike, as billions of financial transactions have accumulated in trade repositories without any ability to aggregate them for risk purposes. New Distributed Ledger Technology (DLT), an underlying technology of the Blockchain, is now being considered for all data identity standards and their use in financial transactions. It should be noted that DLT promises elimination of intermediaries in the financial supply chain while requiring financial market participants to own a secure representation of their own identities. This promising new architecture, born of the digital age seems better suited to the proposed Barcodes of Finance then to the current regulatory driven existing implementations, born of the legacy past.